2013
DOI: 10.4209/aaqr.2012.02.0024
|View full text |Cite
|
Sign up to set email alerts
|

Urban Aerosol Characteristics during the World Expo 2010 in Shanghai

Abstract: During the World Exposition 2010, which ran from May to October, emission control measures were implemented in Shanghai and surrounding areas to improve the air quality. This study evaluated the effects of regional transport on aerosol characteristics under these controlled local emission conditions using a month's worth of observations of the aerosol number size distributions (10 nm-10 μm) and the chemical compositions of the aerosols. Back-trajectories and a Lagrangian dispersion model were combined to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…These results are in agreement with previous studies for Shanghai. Zhang et al (2013) found that local sources and regional transport from the surrounding cities affected haze episode formation in Shanghai. Li et al (2012) reported that under the winter monsoon, the northerly air flows from Hebei, Shandong, Anhui, and Jiangsu provinces carried highconcentration PM 10 to Shanghai.…”
Section: Backward Trajectory and Cluster Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in agreement with previous studies for Shanghai. Zhang et al (2013) found that local sources and regional transport from the surrounding cities affected haze episode formation in Shanghai. Li et al (2012) reported that under the winter monsoon, the northerly air flows from Hebei, Shandong, Anhui, and Jiangsu provinces carried highconcentration PM 10 to Shanghai.…”
Section: Backward Trajectory and Cluster Analysismentioning
confidence: 99%
“…For example, Zhang et al (2013) reported that air masses passing over highly polluted areas (such as Anhui, Jiangxi, Zhejiang, Shandong and Jiangsu provinces) affected air quality at the ground level in Shanghai. found that the majority of PM 2.5 of heavy haze episode in Shanghai was partly contributed by regional transports of pollutants from the upwind adjacent provinces.…”
Section: Source Contributions Based On Pscf and Cwt Analyses For Pm 25mentioning
confidence: 99%
See 1 more Smart Citation
“…This trend could be explained in terms of relative affluence of the urban population in the country. There are reports of pollution reduction after implementation of emission control measures taken prior to big events such as the World Exposition 2010 (Zhang et al, 2013) and the Commonwealth Games 2010 (Kaushar et al, 2013). Though some success has been achieved in terms of noise reduction on implementation of noise standards for firecrackers, such strict emission control measures are not implemented in terms of Diwali celebrations in India.…”
Section: Introductionmentioning
confidence: 99%
“…Besides Lin'an, there were only very limited studies of O 3 made in urban areas in some YRD cities (e.g., Tu et al, 2007;Geng et al, 2008;Ran et al, 2012 ). PM 2.5 measurements in this region have been performed only in recent years (e.g., Fu et al, 2008;Zhou et al, 2009;Li et al, 2011;Huang et al, 2012;Zhang et al, 2013). However, most of these studies were done close to Shanghai, i.e., the eastern YRD, and mainly cover short periods.…”
Section: Introductionmentioning
confidence: 99%